Metal-Free Pyrene-Based Conjugated Microporous Polymer Catalyst Bearing N- and S-Sites for Photoelectrochemical Oxygen Evolution Reaction - Das, Sabuj Kanti; Shyamal, Sanjib; Das, Manisha; Mondal, Saptarsi; Chowdhury, Avik; Chakraborty, Debabrata; Dey, Ramendra Sundar; Bhaumik, Asim (Frontiers in chemistry, 2021)
The development of an efficient, sustainable, and inexpensive metal-free catalyst for oxygen evolution reaction (OER) via photoelectrochemical water splitting is very demanding for energy conversion processes such as green fuel generators, fuel cells, and metal-air batteries. Herein, we have developed a metal-free pyrene-based nitrogen and sulfur containing conjugated microporous polymer having a high Brunauer-Emmett-Teller surface area (761 m 2 g −1 ) and a low bandgap of 2.09 eV for oxygen evolution reaction (OER) in alkaline solution. The π -conjugated as-synthesized porous organic material (PBTDZ) has been characterized by Fourier transform infrared spectroscopy (FT-IR), solid-state 13 C (cross-polarization magic angle spinning-nuclear magnetic resonance) CP-MAS NMR, N 2 adsorption/desorption analysis, field-emission scanning electron microscope (FESEM), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA) experiments. The material acts as an efficient catalyst for photoelectrochemical OER with a current density of 80 mA/cm 2 at 0.8 V vs. Ag/AgCl and delivered 104 µmol of oxygen in a 2 h run. The presence of low bandgap energy, π -conjugated conducting polymeric skeleton bearing donor heteroatoms (N and S), and higher specific surface area associated with inherent microporosity are responsible for this admirable photoelectrocatalytic activity of PBTDZ catalyst.